2002
DOI: 10.5751/es-00444-060215
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Academic Conservation Biology Literature on Endangered Species Recovery Planning

Abstract: ABSTRACT. Despite the volume of the academic conservation biology literature, there is little evidence as to what effect this work is having on endangered species recovery efforts. Using data collected from a national review of 136 endangered and threatened species recovery plans, we evaluated whether recovery plans were changing in response to publication trends in four areas of the academic conservation biology literature: metapopulation dynamics, population viability analysis, conservation corridors, and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 18 publications
0
21
0
1
Order By: Relevance
“…This gap between research and implementation is almost certainly the norm for other subdisciplines of conservation biology (Saunders et al 1991;Pickett et al 1997;Ehrenfeld 2000;Stinchcombe et al 2002;Linklater 2003). For example, Linklater (2003) found that the quantity of scientific literature on endangered rhinoceros increased in response to its decline, but became dominated by ex situ laboratory-based studies despite conservation action plans identifying in situ and ecological studies as priorities.…”
Section: Introductionmentioning
confidence: 99%
“…This gap between research and implementation is almost certainly the norm for other subdisciplines of conservation biology (Saunders et al 1991;Pickett et al 1997;Ehrenfeld 2000;Stinchcombe et al 2002;Linklater 2003). For example, Linklater (2003) found that the quantity of scientific literature on endangered rhinoceros increased in response to its decline, but became dominated by ex situ laboratory-based studies despite conservation action plans identifying in situ and ecological studies as priorities.…”
Section: Introductionmentioning
confidence: 99%
“…of recovery plans has been poor, however, with only 2 percent of USFWS-administered species having achieved more than 75 percent of their recovery objectives (USFWS 2004b). In addition, the plans have been criticized as vague, unlikely to abate threats, and lacking in biological rigor (Schemske et al 1994, Tear et al 1995, Lawler et al 2002, Schultz and Gerber 2002, Stinchcombe et al 2002. The criteria for determining whether species have recovered are often set too low (Tear et al 1993, Foin et al 1998, Doremus and Pagel 2001.…”
Section: Finding 1: Listing Enhances Recovery Over Timementioning
confidence: 99%
“…While Stinchcombe and Moyle (2002) called for greater involvement of academic researchers in preparing species recovery plans to increase the uptake of conservation research in recovery planning, this may be a lesser problem than encouraging the formal publication of information in the grey literature that otherwise risks being overlooked or lost altogether Calver and King (2000). There is also a need for more basic ecological research to inform recovery plans (Ortega-Argueta et al 2011) and for integrating the knowledge and experience of local community groups into research and publication (e.g., Fairfull and Williams 2003).…”
Section: Characteristics Of Sources Cited In Species Recovery Plansmentioning
confidence: 99%